Editorial. Special Issue: Growth of agroholdings and mega-farms in transition and emerging market economies: Institutional and organizational aspects - Taras Gagalyuk; William H. Meyers; Alfons Balmann (International Food and Agribusiness Management Review, 2021)
Since the research agenda on agroholdings and mega-farms was elaborated in the 2017 special issue of IFAMA, much has been learned about structure, performance and management of these farming systems. Despite doubts about the sustainability of these farming systems, they have evolved and even flourished under a wide variety of governance and geographical conditions. It remains to be seen if these systems will be successful in the long run, but continued research is warranted to understand their evolution, functional forms and impacts. This special issue includes four papers examining acquisition, growth and restructuring processes under differing conditions in Brazil, Russia, and Ukraine to gain a deeper and broader understanding of these management forms. A second major focus of this special issue is in the socio-political sphere with three papers to document and better understand the corporate social responsibility of such firms in Argentina, Kazakhstan, Russia and Ukraine. The new knowledge and understanding gained from these papers leads to a reformulation of the research agenda on the development of agroholdings and mega-farms in transition and emerging market economies.
Keywords: Q13; Q14; Q16; 330; agroholdings; mega-farms; management systems; CSR